STEM CELLS: AN APPROACH FOR TREATMENT OF ATHEROSCLEROSIS - Jatav, Vinod Kumar; Sharma, Sunita (Asian Journal of Pharmaceutical and Clinical Research, 2018)
The contribution of stem cells to control atherosclerosis progression and vascular remodeling after injury in humans is established; however, many details are still unknown. The success with stem cell therapies in the treatment of hematological disorders over the past four decades enhanced our understanding of the physiology of vascular remodeling and motivated towards regenerative medicine and therapeutic restoration of the damaged organ. Stem cells isolated from bone marrow are currently being tested for their therapeutic potential in a variety of clinical conditions including cardiovascular injury, kidney failure, cancer, neurological, and bone disorders. The main focus of this review paper is to reveal the role of different types of stem cells such as embryonic stem cell, adult stem cell, smooth muscle progenitor cells, endothelial progenitor cells, mesenchymal stem cells, and vascular smooth muscle cells and find out possibility to use them for the treatment of atherosclerosis as well as to reduce atheroma formation.